From phosphonium salts to binuclear ortho-palladated phosphorus ylides. (17th February 2015) - Naghipour, Ali; Badpa, Khadijeh; Notash, Behrouz
Graphical abstract: The reactions of Pd(OAc)2 with the phosphonium salts [CH3 COCH2 PPh3 ]Cl (1 ) and [ClCH2 COCH2 R]Cl (R = PPh3 (2 ), R = P(PhMe)3 (3 )) lead to binuclear orthopalladated complexes of the type [Pd(CH3 COCHPPh3 )(μ-Cl)]2 (4 ), [Pd(ClCH2 COCHPPh3 )(μ-Cl)]2 (5 ) and [Pd(ClCH2 COCHP(PhMe)3 )(μ-Cl)]2 (6 ). X-ray analysis of5 demonstrates a Cl bridged dimeric structure with C, C-chelated groups. Abstract: This current piece of research presents an easy and direct way for the synthesis of binuclear ortho-palladated phosphorus ylide derivatives of acetone and chloroacetone in high yield and high purity by the reaction of the phosphonium salts [CH3 COCH2 PPh3 ]Cl (1 ) and [ClCH2 COCH2 R]Cl (R = PPh3 (2 ), R = P(PhMe)3 (3 )) with palladium(II) acetate in methanol under mild conditions to afford the dimeric orthopalladated complexes, [Pd(CH3 COCHPPh3 )(μ-Cl)]2 (4 ), [Pd(ClCH2 COCHPPh3 )(μ-Cl)]2 (5 ) and [Pd(ClCH2 COCHP(PhMe)3 )(μ-Cl)]2 (6 ).